The reception of German mysticism in early modern England - Tolan, Daniel J.; Kirby, W. J. Torrance; Hedley, Douglas (Studies in the history of Christian traditions, 2025)
"The volume aims to establish the influence of German or Rhenish mysticism on English religious thought, chiefly in the 17th-century. The English reception of such German mystical authors as Meister Eckhart, the anonymous author of Theologia Germanica, Johannes Tauler, Nicholas of Cusa, Sebastian Franck, Hans Denck, Valentin Weigel, and Jakob Böhme has been hitherto little studied. Such English readers as Henry More, Anne Conway, John Sparrow, John Everard, Giles Randall, and several Cambridge Platonists established a lineage that connected these mystics, and created a philosophical bridge between England and Germany. The volume highlights the international legacy of these mystical writers by adopting the perspective of historico-philosophical engagement with sources, placing them within the theological milieu of their time"--